DEVELOPMENT OF ARABIC-BASED LKPD AT MTS ISLAMIYAH GUNTING SAGA - Pane, Siti Sarah Sitorus; Zulheddi, Zulheddi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This article aims to find out how to develop Arabic- based worksheets with the theme